Implementation of Phylogenetic Worksheet to Improve Students’ Tree Thinking and Critical Thinking Skills on Spermatophyte Classification - Sofi Rahmania; Topik Hidayat; Bambang Supriatno (Lectura : Jurnal Pendidikan, 2023)
Recent research shows that students’ ability to read and create phylogenetic trees (tree thinking) is low, meanwhile phylogenetic analysis has become one of the demands on the 2016 version of the 2013 curriculum. Learning using phylogenetic trees is thought to be able to train critical thinking skills as the demands of the 21st century. However, the use of phylogenetic worksheets, especially on Spermatophyte classification, is often skipped in learning activities at School. This research aims to determine the improvement of students’ tree thinking and critical thinking skills after implementing phylogenetic worksheets in Spermatophyte learning as a visual representation of tree-thinking abilities. This research type was experimental research with one group pretest posttest design that involving 29 students. The research data collection methods were test and interview. The research instruments that used are 25 multiple choice questions of tree-thinking test instrument and 10 essay questions of critical thinking test instrument. Data then analyzed by N-Gain test. The interview was conducted to obtain supporting data. The results showed that learning by implementing phylogenetic worksheets was quite effective in increasing critical thinking skills and tree-thinking skills with an average increase of both in the medium category. As a result, the spermatophyte classification learning using phylogenetic worksheet can be used as an alternative learning activity because it can improve tree thinking and critical thinking skills.